A new species of Dolichopus Latreille, 1796 from Turkey (Diptera: Dolichopodidae) - I.Ya. Grichanov (Кавказский энтомологический бюллетень, 2012)
A new peculiar species Dolichopus zaitzevi Grichanov sp. n. is described from Turkey. It is the closest to Palearctic D. cinctipes Wahlberg, 1850 by modification of mid tibia (male secondary sexual character), but keys to D. vitripennis Meigen, 1824. New data on the distribution of D. cinctipes and D. vitripennis are presented